1992
DOI: 10.1002/ajmg.1320430510
|View full text |Cite
|
Sign up to set email alerts
|

TAR‐like syndrome in a consanguineous Mayan girl

Abstract: We report on a 3-month-old girl with a TAR-like syndrome. Her older brother died with a similar disorder at 3 months of unknown causes. The parents are second cousins of Mayan ancestry. The infant also had, in addition to the usual abnormalities of TAR syndrome, depressed nasal bridge, cataracts, glaucoma, megalocorneae, and blue sclerae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…This ocular anomaly has been reported once before in association with the TAR syndrome but in a consanguineous Mayan girl, who had, in addition to cataract, other ocular anomalies including glaucoma, megalocornea and blue sclera [11]. …”
Section: Discussionmentioning
confidence: 90%
“…This ocular anomaly has been reported once before in association with the TAR syndrome but in a consanguineous Mayan girl, who had, in addition to cataract, other ocular anomalies including glaucoma, megalocornea and blue sclera [11]. …”
Section: Discussionmentioning
confidence: 90%
“…1 2 8-12 Cases associated with consanguinity are rare with only three sib pairs reported. 8 13 14 Other evidence casts doubt on this mode of transmission. Boelskov-Edelberg et al 11 reported a family with a proband affected with typical TAR syndrome.…”
mentioning
confidence: 99%
“…37,38 The Aase syndrome phenotype also includes limb and hematologic manifestations, although the hematologic finding is a form of congenital anemia (Blackfan-Diamond type) and the limb defects include abnormal thumbs which are usually triphalangeal or duplicated. 39 Ceballos-Quintal et al 40 described siblings who were thought to have TAR syndrome, but had additional ocular findings (e.g., glaucoma and cataract). There have also been two reports of infants with apparent TAR syndrome with esophageal atresia; however, it appears that one of those infants was missing thumbs, so this might be a distinct condition from TAR syndrome.…”
Section: Differential Diagnosis Of Tar Syndromementioning
confidence: 99%